Implementasi Digital Signature pada Secure Electronic Prescription menggunakan Digital Signature Algorithm berbasis Android - Hanaria Rotua Tampubolon; Ari Kusyanti; Fariz Andri Bakhtiar (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Medication safety is a term to describe safety precautions from drug use. Medication safety prevents deaths that were caused by drugs that were prescribed wrongly. One of the main causes of wrongly prescribing a drug is the pharmacist not being able to read a doctor's instruction which is not standardized. Such problems can be overcome by using e-prescription, which can be utilized by doctor's and other medical staff to prescribe and send the prescription. However, there are risks of forgery and denial of the e-prescription. Therefore, a security mechanism needs to be installed on the e-prescription to guarantee integrity, authentication, and non-repudiation, which is in the form of a digital signature. This research will explain the design, implementation, security, and performance of the Android based e-prescription using the Digital Signature Algoritm method and SHA-1 as a hash function. The research results test the integrity aspect using a brute force, collision attack, and birthday attack. However, the integrity aspect could not be fulfilled, because the hash function being used which was SHA-1, was very vulnerable to the previously mentioned attack types. To ensure the authentication and non-repudiation aspect, a test was conducted and both aspects were fulfilled. The process of forming and verifying the signature required 6.36963 ms and 11,79276 ms respectively. The implementation of the digital signature on the e-prescription using DSA in this research was considered a success in the authentication and non-repudiation aspects.